Network Management, MIBs and MPLS Principles, Design and Implementation - Morris, Stephen (Pearson, 2003)
Network Management, MIBs and MPLS: Principles, Design and Implementation is the definitive guide to managing and troubleshooting enterprise and service provider networks. This in-depth tutorial from networking expert Stephen Morris delivers clear and concise instruction on networking with MIBs, SNMP, MPLS, and much more. Coverage includes SNMPv3, network management software components, IP routing, HP Openview Network Node Manager, NMS software components, among other key techniques and tools for managing large network systems.
Online resource; Title from title page (viewed June 20, 2003)
Keywords: Computer networks -- Management; Réseaux d'ordinateurs; Gestion; Computer networks; Management